Interactive Mobile Apps (CinTA 2.0) for Dyslexia’s Children Malay Language Therapy Tool: Focus on Malay Language - Hasni Nasrudin, Nur; Ahmad Junid, Rosida; Khatijah Nor Abdul Rahim, Siti; Mohamed, Zainab; Zafirah Azmi, Anis; Imaina Abdullah, Ini (International Journal of Engineering and Technology, 2018)
The implementation of mobile apps in the educational systems has kept abreast with the needs of specific learning disability (SLD) children. It was agreed by researchers that technology is able to aid and harness the language development of these children. The use of mobile applications in English language has been widely accepted and implemented among educators. However, it was discovered that most of the applications have scarcely adopted the Malay language as the main stream to aid Malay language development of these children. Thus, it is imperative to set the aim of this paper to introduce an interactive mobile apps that uses Malay Language as the Therapy Tool for the Dyslexic Children in improving their language learning processes. The uniqueness of this app falls on the aesthetic value that is implemented in CInTA 2.0. The app is user friendly which applied multi-sensory technique that is suitable for learners with language disorder, specifically dyslexic children.Â Â